2020
DOI: 10.1002/ppap.201900186
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure Townsend discharges as a promising tool for the one‐step deposition of antifogging coatings from N2O/TMCTS mixtures

Abstract: The need to ensuring the "see-through" property of transparent materials when exposed to sudden temperature changes or very humid conditions has encouraged the development of antifogging strategies, such as the deposition of (super) hydrophilic coatings. However, despite the effectiveness of these coatings in combating the effects of fogging, most of the coating techniques explored to date are typically time-consuming and environment-unfriendly. Bearing this in mind, we demonstrate that the application of diel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The ATR-FTIR spectra (Figure 3c) indicated that the pSiNPs made in the SB (SB-pSiNPs) had a somewhat higher degree of oxidation than that of the AC-pSiNPs, which is consistent with the longer reaction time and higher temperature of the SB sonication process. The infrared spectrum of both types of pSiNPs displayed two characteristic bands associated with surface hydrides: ν(Si−H) stretching at 2050−2100 cm −1 , 29 δ(Si−H) bending at 873 cm −1 , 30 and ρ(Si−H) rocking at 621 cm −1 and surface oxides: ν(Si−O−Si) stretching at 1100−1000 cm −1 . 31,32 In addition, TEM images of SB-pSiNPs and AC-pSiNPs showed that both nanoparticle types had similar sizes and porous nanostructures, with average pore sizes of 20.58 ± 4.47 nm for SB-pSiNPs and 19.72 ± 3.82 nm for AC-pSiNPs (Figures 3d and S5).…”
Section: Comparison Of Psinps Prepared With a Sb Vs An Ac Systemmentioning
confidence: 99%
“…The ATR-FTIR spectra (Figure 3c) indicated that the pSiNPs made in the SB (SB-pSiNPs) had a somewhat higher degree of oxidation than that of the AC-pSiNPs, which is consistent with the longer reaction time and higher temperature of the SB sonication process. The infrared spectrum of both types of pSiNPs displayed two characteristic bands associated with surface hydrides: ν(Si−H) stretching at 2050−2100 cm −1 , 29 δ(Si−H) bending at 873 cm −1 , 30 and ρ(Si−H) rocking at 621 cm −1 and surface oxides: ν(Si−O−Si) stretching at 1100−1000 cm −1 . 31,32 In addition, TEM images of SB-pSiNPs and AC-pSiNPs showed that both nanoparticle types had similar sizes and porous nanostructures, with average pore sizes of 20.58 ± 4.47 nm for SB-pSiNPs and 19.72 ± 3.82 nm for AC-pSiNPs (Figures 3d and S5).…”
Section: Comparison Of Psinps Prepared With a Sb Vs An Ac Systemmentioning
confidence: 99%
“…As can be seen, the coatings are different from those generally produced in classical N 2 Townsend discharge with HMDSO. [ 49,54,55 ]…”
Section: Characterization Of the Organosilicon Coatings Deposited Wit...mentioning
confidence: 99%
“…As can be seen, the coatings are different from those generally produced in classical N 2 Townsend discharge with HMDSO. [49,54,55] For 1 min, the image displayed in Figure 2 shows that the coating consists in micrometer spots dispersed on the substrate surface. Moreover, while the films obtained with continuous injection of fully vaporized HMDSO are generally smooth, [56,57] Figure 2 reveals that the ones obtained with pulsed HMDSO injection at longer times are viscous and macroscopically inhomogeneous.…”
Section: Characterization Of the Organosilicon Coatings Deposited Wit...mentioning
confidence: 99%